CAPITAL RESERVE MANAGEMENT OF PUBLIC COMPANIES: ACCOUNTING TOOLS AS INFORMATION FUNCTION OF TARGET MECHANISM - Olesia Lemishovska (Baltic Journal of Economic Studies, 2021)
The purpose of the article is to present the financial and economic content and purpose of capital reserves, insurance funds to ensure future costs and payments as the main components of the reserve system of public companies. The methods of theoretical and comparative analysis allowed to expand the view of the objects of reservation in the global space by comparing the norms of international standardization of financial reporting and the mandatory requirements of individual states in the field of reservation. The research methodology covers the analysis of reserved sources for Ukrainian and global companies in the context of the large-scale socio-economic crisis caused by the global COVID-19 pandemic. Based on a comparative assessment of the potential of reserve sources of surveyed companies, reservation in today’s crisis economy and in the foreseeable future is one of the most necessary and important means of ensuring the stable operation of socially significant companies. The study of regulatory norms of different states and principles and norms of standardization of public financial reporting led to the conclusion that for internal management purposes and market counterparties and public administration in the face of increasing unpredictability and depth of risk requires a more detailed and reliable information base on existing modern companies reserved funds to overcome the risks of loss (reduction) of capital. The practical consequences of weak imperatives on the obligation to create reservation facilities have been reflected in the allocation of subsidies from the state budgets of different countries to commercial structures in many areas of the economy. The existing issues actualize multi-vector developments in the system of interdisciplinary research, which substantiates the scientific legitimacy and relevance of our study. The results of analytical and logical approaches in assessing the state of backup support for Ukrainian and well-known international companies became the basis for obtaining evidence and arguments in formulating the parameters of adequate information for the current needs of targeted management of backup processes. The methods of verification of reserve system components proposed in this study can be used to establish general trends in the development of information parameters (accounting and public reporting system) in the field of reserve management and future losses (reduction) of capital of modern public companies.